2014
DOI: 10.1111/hequ.12051
|View full text |Cite
|
Sign up to set email alerts
|

European Mobility of United Kingdom Educated Graduates. Who Stays, Who Goes?

Abstract: Official figures from the Home Office show an increase in mobility of the highly-skilled from the United Kingdom (UK) to other European countries. This paper analyses the social composition of intra-European mobile graduates from the UK in the context of recent political developments (Bologna-Process, European Higher Education Area). Using quantitative and qualitative data from a longitudinal study of students and its follow-up study, the paper compares the social composition and current activity of intra-Euro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 23 publications
0
12
0
1
Order By: Relevance
“…Currently, mobility within Europe is characterised by a high proportion of highly skilled workers (Recchi and Favell, 2009); its possible re-occurrences (Ackers and Gill, 2009), and the value it adds to previously acquired skills and knowledge (Murphy-Lejeune, 2002, Behle 2014. Mobility fulfils different functions for individual graduates and in the process of creating a joint European Higher Education Area.…”
Section: The Wider Picture: Characteristics and Functions Of Mobilitymentioning
confidence: 99%
See 4 more Smart Citations
“…Currently, mobility within Europe is characterised by a high proportion of highly skilled workers (Recchi and Favell, 2009); its possible re-occurrences (Ackers and Gill, 2009), and the value it adds to previously acquired skills and knowledge (Murphy-Lejeune, 2002, Behle 2014. Mobility fulfils different functions for individual graduates and in the process of creating a joint European Higher Education Area.…”
Section: The Wider Picture: Characteristics and Functions Of Mobilitymentioning
confidence: 99%
“…The authors found that extensiveness of multicultural experiences is positively related to creative performance (in terms of insight learning, remote association, and idea generation) and creativity-supporting cognitive processes (i.e. retrieval of unconventional knowledge, recruitment of ideas from unfamiliar cultures for creative idea expansion) (Leung et al, 2008 (BEHLE, 2014).…”
Section: Individual Benefits and Skill Gainsmentioning
confidence: 99%
See 3 more Smart Citations